2020
DOI: 10.1007/s10549-020-05687-2
|View full text |Cite
|
Sign up to set email alerts
|

HER2-targeted therapy influences CTC status in metastatic breast cancer

Abstract: Purpose As an independent, negative-prognostic biomarker for progression-free survival (PFS) and overall survival (OS), circulating tumor cells (CTCs) constitute a promising component for developing a liquid biopsy for patients with metastatic breast cancer (MBC). The effects of HER2-targeted therapy such as trastuzumab, pertuzumab, T-DM1, and lapatinib on CTC status and longitudinal enumeration were assessed in this trial. Methods CTC status of 264 patients with MBC was analyzed prior to and after 4 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…One example for quantitative differences in protein amounts relates to circulating tumor cell (CTC) analysis. It was reported that studying Her2 and EpCAM expression in CTCs could guide personalized anticancer therapy. , In addition, protein post-translational modifications (PTMs) occur during or after protein biosynthesis that dramatically alter the functionality of proteins. Investigation of the imbalance in protein PTMs is particularly important for various diseases such as cancers, diabetes, and neurodegenerative disorders .…”
Section: Introductionmentioning
confidence: 99%
“…One example for quantitative differences in protein amounts relates to circulating tumor cell (CTC) analysis. It was reported that studying Her2 and EpCAM expression in CTCs could guide personalized anticancer therapy. , In addition, protein post-translational modifications (PTMs) occur during or after protein biosynthesis that dramatically alter the functionality of proteins. Investigation of the imbalance in protein PTMs is particularly important for various diseases such as cancers, diabetes, and neurodegenerative disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Second, in a small sample size with second blood draws (n = 14), we showed the dynamic change of CTC enumeration and CTC-HER2 phenotypes after the combination therapy. As expected, the depletion of epithelial CTCs was far from a practical predictive biomarker of the treatment outcomes [61]. A few groups investigated the clinical significances of evolutionary HER2 status on CTCs.…”
Section: Discussionmentioning
confidence: 92%
“…Since our results show that the number of HER2+ cells decreased between times of collection in patients under anti-HER2 targeted therapy, it may suggest a positive response to therapy. The higher number of CTCs in total by one of the patients (patient 1) may be indicative that the tumour burden is still high, but tumour phenotypical characteristics have changed, ideally even to a less invasive and more well managed subtype [88,89]. The presence of HER2+ cells, isolated by the RUBYchip™, in patients that were not diagnosed as having HER2+ tumours by the tissue biopsy analysis was observed.…”
Section: Discussionmentioning
confidence: 95%